2020
DOI: 10.1155/2020/2524174
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Metformin against Hydrogen Peroxide-Induced Oxidative Damage in Human Retinal Pigment Epithelial (RPE) Cells by Enhancing Autophagy through Activation of AMPK Pathway

Abstract: Age-related macular degeneration (AMD) is a leading cause of blindness with limited effective treatment. Although the pathogenesis of this disease is complex and not fully understood, the oxidative damage caused by excessive reactive oxygen species (ROS) in retinal pigment epithelium (RPE) has been considered as a major cause. Autophagy is essential for the degradation of cellular components damaged by ROS, and its dysregulation has been implicated in AMD pathogenesis. Therefore, strategies aiming to boost aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…The AMPK signaling activation ameliorated autophagy and the level of coactivator-associated arginine methyltransferase 1 (CARM1), which involves several cellular processes, including autophagy in the aging heart [ 75 ]. Metformin can stimulate autophagy via activating AMPK signaling to protect human retinal pigment epithelial cells from hydrogen peroxide induced-oxidative stress [ 76 ]. In a d -galactose-induced renal aging model, hyperoxide attenuated a renal injury by augmenting autophagy through AMPK/ULK1 signaling [ 77 , 78 ].…”
Section: Ampk Signalingmentioning
confidence: 99%
“…The AMPK signaling activation ameliorated autophagy and the level of coactivator-associated arginine methyltransferase 1 (CARM1), which involves several cellular processes, including autophagy in the aging heart [ 75 ]. Metformin can stimulate autophagy via activating AMPK signaling to protect human retinal pigment epithelial cells from hydrogen peroxide induced-oxidative stress [ 76 ]. In a d -galactose-induced renal aging model, hyperoxide attenuated a renal injury by augmenting autophagy through AMPK/ULK1 signaling [ 77 , 78 ].…”
Section: Ampk Signalingmentioning
confidence: 99%
“…Metformin (MET) is an oral antidiabetic biguanide agent derived from Galega officinalis that not only reduces blood glucose levels and improves insulin sensitivity but also has benefits against cardiovascular diseases [21][22][23][24]. Several studies have shown that MET appears to reduce excessive ROS production and limit early apoptosis [25,26]. Whether MET can reduce MGOinduced EC apoptosis, what roles MET and MGO play, and how MET and MGO interact with each other in the context of the cardiovascular protective effects of MET remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factor EB (TFEB) inducer trehalose protects RPE against oxidative damage and cell death by upregulating autophagy ( Abokyi et al, 2020 ). Metformin defenses hydrogen peroxide-induced oxidative damage in RPE by enhancing autophagy through activation of the AMP-activated protein kinase (AMPK) pathway ( Zhao et al, 2020 ). Two recent studies described that SOCS2 is involved in autophagy in myocardial I/R and Huntington’s disease ( Li et al, 2019 ; Cho et al, 2021 ), but the underlying molecular mechanisms for SOCS2 regulating autophagy are unclear.…”
Section: Discussionmentioning
confidence: 99%